ANALISIS KESALAHAN SISWA KELAS 9 MTS DDI BANUA DALAM MENGERJAKAN SOAL MATEMATIKA - Maria Ulfah; Astrid B; Nurul Musthafiyah Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the errors of MTs students in solving statistical material problems. The research method used in this study is the description method. The study was conducted with the research subjects of 25 students of class IXc Nurul Iman Sindangkerta in the 2019/2020 school year. The test questions were 5 questions. The results showed that the students' mathematical abilities in terms of overall results were classified as low and there were 1 indicators that answered a lot correctly, which were indicators that correctly identified a problem, which was 65%. And it consists of 1 indicator that enters a lot of answers which is 81% with indicators explaining the steps or ideas of a problem solving clearly and precisely into written form.